Eco-Driven Desire: The Synergy of Brand Image and Emotion in Cultivating Loyal Consumers - Pramadanti, Rindika; Gultom, Masrina; Sihombing, Rusman Effendi (Indonesian Journal of Social Research (IJSR), 2025)
This study investigates the influence of green marketing, brand image, and emotional desire on customer satisfaction and loyalty within the context of McDonald's, a leading brand in the fast-food industry. In response to growing environmental awareness and intense market competition, companies are increasingly required not only to offer high-quality products but also to foster emotional connections and build strong, positive brand images in the minds of consumers. Employing a quantitative approach, this research uses a survey method targeting consumers of environmentally friendly products. The population comprised customers who had made at least two purchases at McDonald’s, and data were collected using a purposive sampling technique, yielding a total of 225 respondents. Questionnaires were distributed between February and April 2025, and data were analyzed using the SmartPLS software. The findings reveal that green marketing, brand image, and emotional desire significantly influence customer satisfaction. Moreover, brand image and emotional desire directly impact customer loyalty, while green marketing does not have a direct effect. Emotional desire also indirectly positively affects customer loyalty through the mediating role of customer satisfaction. However, green marketing and brand image do not exhibit significant indirect effects through customer satisfaction. This study contributes to understanding emotional and sustainability-related drivers of customer loyalty in the fast-food sector. It offers practical implications for marketers and business practitioners, emphasizing the need to integrate emotional engagement and environmentally responsible strategies to enhance customer loyalty.